Sweet's syndrome in association with Crohn's disease. Issue 901 (1st November 2000) - Vaz, A; Kramer, K; Kalish, R A
Abstract : A case of Sweet's syndrome in association with Crohn's disease in a young woman is reported. Sweet's syndrome is a rare extraintestinal manifestation of Crohn's disease and ulcerative colitis.